2024
DOI: 10.1021/acs.jpcb.4c00845
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Molecular Dynamics System Size for Increased Precision and Efficiency for Epoxy Materials

Khatereh Kashmari,
Sagar U. Patil,
Josh Kemppainen
et al.

Abstract: Molecular dynamics (MD) simulation is an important tool for predicting thermo-mechanical properties of polymer resins at the nanometer length scale, which is particularly important for efficient computationally driven design of advanced composite materials and structures. Because of the statistical nature of modeling amorphous materials on the nanometer length scale, multiple MD models (replicates) are typically built and simulated for statistical sampling of predicted properties. Larger replicates generally p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…The models generated for both the DGEBF/DETDA system and the cyanate ester system were greater than 20,000 atoms; as Kashmari et al 73 have recently shown for an epoxy system, a minimum of 15,000 atoms was the ideal balance between computational efficiency and accuracy for thermomechanical property predictions. In total, six different packing methods were studied and are visualized in Figure 9 .…”
Section: Lunar Benchmark Systems and Modeling Methodsmentioning
confidence: 96%
“…The models generated for both the DGEBF/DETDA system and the cyanate ester system were greater than 20,000 atoms; as Kashmari et al 73 have recently shown for an epoxy system, a minimum of 15,000 atoms was the ideal balance between computational efficiency and accuracy for thermomechanical property predictions. In total, six different packing methods were studied and are visualized in Figure 9 .…”
Section: Lunar Benchmark Systems and Modeling Methodsmentioning
confidence: 96%